PENINGKATAN PENGETAHUAN PETANI DALAM PENGOLAHAN PRODUK HILIR KAKAO DI KECAMATAN RANTAU PEUREULAK - Muslimah Muslimah; Fiddini Alham; Siti Komariyah; Nova Purnama Lisa (Universitas Mataram, 2023)
Exports of cocoa beans that are larger than processed cocoa indicate that Indonesia has lost a lot of potential added value from the cocoa processing industry. The potential or opportunity for added value through the cocoa processing industry has disappeared due to the relatively high price difference between the beans and the processed cocoa produced. Processing can also increase the income and welfare of farmer groups in this service.This service was aimed to determine the level of knowledge development of farmer group pre and post extension service and workshop about the development of downstream cocoa product in Tanjung Tani Village, Rantau Peureulak Subdistrict, East Aceh Regency.The methods applied in this study are: Socialization and workshops. The stages are as follows: participants are given a pre test, then given socialization (counseling), the method used in socialization is lectures, after being given socialization the participants are given a workshop (direct practice), then the last stage is given a post test.Based on the result of pre-test and post-test, scores were obtained to determine the level of knowledge development of samples pre and post extension service and workshop. The data collected were processed using Wilcoxon Signed Test (non-parametric statistics) at Î±= 5%, with criteria for decision making that is accepted if significance level â‰¥ Î±, is accepted if significance level < Î± . The result showed that significance level of (0,016) < Î±_0,05. To conclude, was rejected and was accepted, indicating a significant difference of farmers' level of knowledge pre and post extension service and workshop.